Relationship of Pneumocystis antibody responses to paediatric asthma severity. Issue 1 (24th March 2021) - Rayens, Emily; Noble, Brenda; Vicencio, Alfin; Goldman, David L; Bunyavanich, Supinda; Norris, Karen A
Abstract : Background: Although asthma is the most commonly diagnosed respiratory disease, its pathogenesis is complex, involving both genetic and environmental factors. A role for the respiratory microbiome in modifying asthma severity has been recently recognised. Airway colonisation by Pneumocystis jirovecii has previously been associated with multiple chronic lung diseases, including chronic obstructive pulmonary disease (COPD) and severe asthma (SA). Decreased incidence of Pneumocystis pneumonia in HIV-infected individuals and reduced severity of COPD is associated with naturally occurring antibody responses to the Pneumocystis antigen, Kexin (KEX1). Methods: 104 paediatric patients were screened for KEX1 IgG reciprocal end point titre (RET), including 51 with SA, 20 with mild/moderate asthma, 20 non-asthma and 13 with cystic fibrosis (CF) in a cross-sectional study. Results: Patients with SA had significantly reduced Pneumocystis KEX1 titres compared with patients with mild/moderate asthma (p=0.018) and CF (p=0.003). A binary KEX1 RET indicator was determined at a threshold of KEX1 RET=1000. Patients with SA had 4.40 (95% CI 1.28 to 13.25, p=0.014) and 17.92 (95% CI 4.15 to 66.62, p<0.001) times the odds of falling below that threshold compared with mild/moderate asthma and patients with CF, respectively. Moreover, KEX1 IgG RET did not correlate with tetanus toxoid IgG (r=0.21, p=0.82) or total IgE (r=0.03, p=0.76), indicating findings are specific to antibody responses to KEX1. Conclusions: Paediatric patients with SA may be at higher risk for chronic Pneumocystis infections and asthma symptom exacerbation due to reduced levels of protective antibodies. Plasma KEX1 IgG titre may be a useful parameter in determining the clinical course of treatment for paediatric patients with asthma.